Turnover intention of employees, supervisor support, and open innovation: The role of illegitimate tasks - Aamar Ilyas; Ahmed Hussain Khan; Farah Zaid; Muhammad Ali; Asad Razzaq; Waris Ali Khan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Recently, the small and micro enterprises have earned significant fame in the management and entrepreneurship discipline. Researchers have examined the turnover intention of employees working within formal organizations, but ignored the employees working within small and micro enterprises. The aim of this study is to analyze the moderating effects of supervisor support on the relationship between illegitimate tasks and turnover intention of the employees of small and micro enterprises. An interview-administered questionnaire approach was used for data collection, and the snowball sampling technique was employed in this study to contact employees who were working within small and micro enterprises. The sample size was 420 employees from Lahore city (the provincial capital city of Punjab, Pakistan). Results showed that supervisor support would moderate the impact of illegitimate tasks on turnover intention, and a high level of support available from supervisor to the employee at the workplace would make them less likely to leave the organization as opposed to an employee who has less supervisor support at the workplace. The study reveals that supervisor support in small and micro enterprises is necessary to reduce or eliminate stress in the environment. Consequently, this study implies that the managers and supervisors of small and micro enterprises should provide logic and explanation to their subordinates and motivate their subordinates as to why they are assigned that particular task instead of any other employee and how important it is. This study contributes to the field of small and micro enterprises by evaluating the relationship between illegitimate tasks and turnover intention. This study is unique because management scholars have more often studied employees' behavior in large corporations rather than in small and micro enterprises.
Keywords: 650; open innovation; illegitimate tasks; Pakistan; small and micro enterprises; supervisor support; turnover intention